Capacity of an electronic portfolio to promote professionalism, collaboration and accountability in educational leadership. - Dixon, Kathryn; Dixon, R. (2009)
This chapter is the result of an investigation into the capacity of an electronic portfolio (e-folio) to promote reflection and collaboration in a process of educational leadership. A cohort (n=11) of volunteer aspirant and current school leaders participated in the trial of an innovative software package designed to facilitate the creation of an electronic portfolio. The research has followed the development of the volunteer group as they underwent the process of constructing an e-folio, in an effort to understand the efficacy of an electronic portfolio as a tool for demonstrating self-reflection, analysis of personal leadership, and collaborative practice. The trial members recorded their reflections regarding their experiences as leaders into their portfolios using the parameters of the "Leadership Framework" as the conceptual guide. This chapter focuses on the results of a content analysis conducted on individual reflections, which found collaborative practice as a key performance indicator in the discharge of educational leadership responsibilities.